Pendidikan Karakter dalam Al-Quran: Membangun Generasi Berakhlak Mulia - Parpatih, Sultan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Quran-based character education plays an important role in shaping individuals with noble character and high integrity. This study aims to analyze the concept of character education in the Quran, identify the main values in personality formation, and explain the implementation strategy in families, schools, and communities. The method used is qualitative research with a literature approach. The results show that character education in the Quran includes key values such as taqwa, honesty (sidq), trustworthiness, patience, gratitude, justice, ihsan, and tawadhu'. Its implementation involves the family as the first educator, schools that integrate Qur'anic values in the curriculum, and communities that build a social environment based on Islamic values. Challenges in the implementation include lack of understanding from parents, limited resources in schools, and social change. The contribution of this study is to provide insight into the importance of Qur'an-based character education in facing modern moral challenges. Future research is suggested to explore empirical data and adaptation strategies in the digital era to improve the effectiveness of character education implementation in daily life.